Internet Access Using Ethernet over PDH Technology for Remote Area - Enceng Sulaeman; Tris sutrisno (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
There was still is gap among people living in city and in remote area to get information access, especially who lived in the Eastern part of Indonesia. People living in such remote area usually were isolated from town by natural condition like rivers, valleys, hills and so on.. Therefore, telecommunication  infrastructure for remote area using cooper was not effective and efficient way to build. The issue was how  information and communication technology could penetrate such areas. This research aimed to propose technology that could be implemented to overcome the difficulties. Ethernet over Plesiochronous Digital Hierarchy (EoPDH) was one of many techniques that provided Ethernet connectivity over non-Ethernet networks.  EoPDH was a standardized methodology for transporting native Ethernet frames over the existing established PDH transport technology.  To provide last milefor the local people, use of Mesh Wireless Local Area Network was made and connected to internet gateway via Ethernet over PDH based microwave radio link. The test showed that The Ethernet frames were successfully transported to remote area with good quality of service such as throughput, response time, and transaction rate. DOI: http://dx.doi.org/10.11591/telkomnika.v13i2.7036